The Hamburg Lectures on Maritime Affairs 2007 & 2008 - Basedow, Jürgen (Springer-Verlag Berlin Heidelberg, 2010)
In 2007, the International Max Planck Research School for Maritime Affairs and the International Tribunal for the Law of the Sea (ITLOS), both based in Hamburg, decided to establish an annual lecture series, the 'Hamburg Lectures on Maritime Affairs' - giving distinguished scholars and practitioners the opportunity to present and discuss recent developments in the field of maritime affairs. The present volume collects seven of the lectures held in 2007 and 2008 by Thomas A. Mensah, Krijn Haak, Sergio M. Carbone, Lorenzo Schiano di Pepe, Erik Rosag, Frank Smeele, Carlos Esplugues Mota and Luciu
Description based upon print version of record
Keywords: Konferenzschrift; Hamburg; Seeschifffahrtsrecht